Chemodynamics on BCDs - Campuzano Castro, Federico (2018)
This work presents a brief summary of the analysis we are performing on the physical and chemical properties of the ionizing gas in star-forming regions belonging to 2 Blue Compact Dwarf galaxies (BCDs), using high resolution echelle spectra. Our aim is to perform a detailed study of the Chemodinamics on BCDs galaxies. To do that, we use the LMFIT (python tool), Pyneb (Luridiana et al. 2015) and our own code (Hagele et al. 2008). We deconvolve the emission-line profiles fitting several gaussians to the different kinematical components to be able to estimate the properties and the nature of the ionized gas. Our next step is to use our kinematical information to performe the chemical abundance analysis and to infer the physical properties of the gas (the chemodynamical study) by using the metodology published in Hagele et al. (2012).